A S‐Arylation of 2‐Mercaptoazoles with Diaryliodonium Triflates under Metal‐Free and Base‐Free Conditions. Issue 8 (6th June 2016) - Zhang, Bianxiang; Kang, Yongqiang; Yang, Lihua; Chen, Xia
Abstract: Heterocyclic aryl sulfides have been widely studied as a monomer or an intermediate for drug synthesis in the field of medicine and materials. The common synthetic processes for preparing aryl sulfides involve transition metals and strong bases. Here, we report a synthetic method for heterocyclic arylsulfides is accomplished by S‐arylation of 2‐mercapto‐substituted aromatic heterocycles with diaryliodonium triflates in high yields. The procedure involves only mixing 2‐mercapto‐aromatic heterocycles and diaryliodonium triflates in DMF at 130 ºC for 24 h under air atmosphere. The most prominent advantage of this method is that all of the ligands, catalysts, bases and any additives are unnecessary. A highly efficient green approach to heterocyclic aryl sulfides was described and the reaction mechanism was discussed. Abstract : A metal‐free and base‐free S‐arylation of 2‐mercaptoaromatic heterocycle has been developed. The reaction proceeds in high yields without excess reagents in the simple reaction conditions by diaryliodonium triflates as an arylating reagent.